Social Safety Concept: Exploring Human Values, Justice, and Sharia - M Muthoifin; Kyeyune Hamidu; Aliem Amsalu; Jihan Husna Srifyan (Solo International Collaboration and Publication of Social Sciences and Humanities, 2024)
This study aims to explore the concept of social safety in the context of human values, justice, and sharia in Islam. This is done to understand how Islamic principles can make a significant contribution to the development and implementation of effective and inclusive social safety. Research Methods in the form of qualitative approaches. Data was collected through literature study, document analysis, as well as interviews with experts and practitioners who have in-depth knowledge of the concept of social safety and the principles of sharia in Islam. Data were analyzed using an inductive approach to identify key themes related to humanity, justice, and sharia in the context of social safety. The results showed that the concept of social safety in Islam is closely woven with human values, justice, and sharia. Principles such as solidarity, mutual aid, and distributive justice are the main foundations in building social safety oriented towards the weak and poor. The implementation of this concept requires cooperation between the government, society, and the private sector to provide holistic and sustainable social protection for all citizens. This research highlights the importance of incorporating human, justice, and sharia values in the development and implementation of social safety. By understanding and applying these principles, it is hoped that a more effective, fair, and sustainable social safety system can be created, which enables each individual to achieve his or her welfare and dignity as a human being.